2005
DOI: 10.1038/sj.ijir.3901364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction in thyroid disorders: comparison with control subjects and with obese and diabetic patients

Abstract: Diagnosis of erectile dysfunction (ED) requires anamnestic investigation, being rarely spontaneously declared by patients. ED occurs frequently in diabetes mellitus, and anecdotal evidence suggests that ED occurs in obesity and in hypothyroidism. The aim of this study was to evaluate the prevalence of ED in patients affected by thyroid disorders (hypothyroidism and hyperthyroidism), in comparison with control subjects and with patients at risk for ED, such as patients with obesity and with type II diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
4
29
0
3
Order By: Relevance
“…23,27,40 The IIEF-5 questionnaire is easily self-administered and can reliably determine the effectiveness of ED treatments. 40,41 In our study population, approximately 50, 17 and 9% of participants with ED had mild, moderate and severe ED, respectively, which is significantly higher than 29, 2.2 and 1.3%, respectively, reported by Ponholzer et al, 27 who also used the IIEF-5 to assess ED in their study of the general population in Austria.…”
Section: Ed Diabetes and Viagra G Yang Et Almentioning
confidence: 58%
“…23,27,40 The IIEF-5 questionnaire is easily self-administered and can reliably determine the effectiveness of ED treatments. 40,41 In our study population, approximately 50, 17 and 9% of participants with ED had mild, moderate and severe ED, respectively, which is significantly higher than 29, 2.2 and 1.3%, respectively, reported by Ponholzer et al, 27 who also used the IIEF-5 to assess ED in their study of the general population in Austria.…”
Section: Ed Diabetes and Viagra G Yang Et Almentioning
confidence: 58%
“…Viswanathan et al, [2] Al-Hunayan A et al, [12] and Veronelli A et al, [14] have all reported that increased BMI had an association with a higher incidence of ED. This same result was reported by Tamler R. et al, [15] In a study done by Viswanathan et al, [2] it was found severe ED was associated with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…To our limited knowledge, Italian researcher Pontiroli firstly established the brief relation between thyroid hormone metabolic disorders and erectile dysfunction 25 . Then revealed increased prevalence of female sexual dysfunction (FSD) in hypothyroid subjects related with cardiovascular risk factors 26 .…”
Section: Discussionmentioning
confidence: 99%